'You all go to check there'. (16th February 2021) - Sonoda, Koji
Abstract : Previous studies of children's directive use in peer interaction have paid attention to practices related to hierarchical relationships. This study demonstrates egalitarian directive use by Baka hunter–gatherer children engaged in giant rat hunting as a group activity. Self-selection and 'you all do' construction were identified as the ways they proceeded with this activity. These two egalitarian directives were not limited to specific persons with authority or power; rather, the children interacted with each other on an equal footing using these forms. Trajectories of action described the difficulties of being in an authoritative position in during activity. This study identified alternative ways to construct equal footing in children's group activities.